Jet lag in athletes after eastward and westward time-zone transition - Lemmer, Björn; Kern, Ralph-Ingo; Nold, Gudrun; Lohrer, Heinz (Chronobiology international, 2002)
In healthy male top athletes several functions were measured after either a westbound flight over six time-zones (WEST: Frankfurt-Atlanta; n=13) or an eastbound flight over eight time-zones (EAST: Munich-Osaka; n=6). Under either condition the athletes performed two standardized exercise training units in the morning and in the afternoon within 24 h, investigations were done as controls in Germany and on day 1, 4, 6, and 11, after arrival. The primary aim of the study was to evaluate the effect of time-zone transitions on the 24h profiles of blood pressure (BP) and heart rate (HR) using an ambulatory BP device (SpaceLabs 90207), for up to 11 d after arrival at the destination. As additional parameters, we studied jet-lag symptoms, training performance, and training coordination by using visual analog scales. Finally, oral temperature and grip strength were measured, and saliva samples were analyzed for cortisol and melatonin. The study showed that all functions were disturbed on the first day after arrival at the destination, jet-lag symptoms remained until day 5-6 after WEST and day 7 after EAST, training performance was worst within the first 4 d after WEST. In accordance with earlier reports, cortisol, melatonin, body temperature, and grip strength were affected in their 24h profiles and additionally modified by the training units. Surprisingly, BP and HR were not only affected on the first day but also the time-zone transition led to an increase in BP after WEST and a decrease in BP after EAST. However, the training units seemed to influence the BP profile more than the time-zone transitions. HR rhythm was affected by both time-zone transitions and exercise. It is concluded that not only jet-lag symptoms but also alterations in physiological functions should be considered to occur in highly competitive athletes due to time-zone transition and, therefore, an appropriate time of reentrainment is recommended.
Published online: 07 Jul 2009
Elektronische Reproduktion der Druck-Ausgabe
Gesehen am 07.04.2022